2007
DOI: 10.1103/physrevc.76.051001
|View full text |Cite
|
Sign up to set email alerts
|

Solutions of nuclear pairing

Abstract: We give the exact solution of orbit dependent nuclear pairing problem between two nondegenerate energy levels using the Bethe ansatz technique. Our solution reduces to previously solved cases in the appropriate limits including Richardson's treatment of reduced pairing in terms of rational Gaudin algebra operators.Pair correlations are manifest in a remarkable range of quantum many-body systems. Originally the idea of pairing and the methods were developed in the context of superconductivity in macroscopic sys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…In between these extreme regimes of synchronized and MSW oscillations, large scale flavor transformation can take place when the neutrino self interaction potential approaches the vacuum oscillation scale [31,32] and the neutrinos and antineutrinos enter the transition region nearly in flavor eigenstates, e.g. [31][32][33][34][35][36][37][38][39]. During the transition, the neutrinos and antineutrinos are said to be "locked" as their survival probabilities mirror each other and the phenomenon is referred to as "bipolar" or "nutation" oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…In between these extreme regimes of synchronized and MSW oscillations, large scale flavor transformation can take place when the neutrino self interaction potential approaches the vacuum oscillation scale [31,32] and the neutrinos and antineutrinos enter the transition region nearly in flavor eigenstates, e.g. [31][32][33][34][35][36][37][38][39]. During the transition, the neutrinos and antineutrinos are said to be "locked" as their survival probabilities mirror each other and the phenomenon is referred to as "bipolar" or "nutation" oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the neutrino-neutrino forward scattering potential [4][5][6], neutrino flavor transformation in the early universe and near the supernova core can be very different from that in the vacuum or in an ordinary matter background only [7][8][9][10][11][12][13][14][15][16][17]. Recent analytical and numerical studies have revealed a new paradigm for neutrino flavor transformation in supernovae [18][19][20][21][22][23][24][25][26], one which is completely different from vacuum oscillations or the conventional Mikheyev-Smirnov-Wolfenstein (MSW) mechanism [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it can also contribute to the flavor evolution in the atmosphere above a proto-neutron star in core-collapse supernovae. There are still many open questions beyond those known in the approximate approach [33,34,35]. Further theoretical and numerical studies are required.…”
Section: Constraints On the Neutrino Oscillationmentioning
confidence: 99%